JUVENILE FISHERY OF GONIALOSA MANMINA IN HIRAKUD RESERVOIR, INDIA: RELEVANCE OF SEASONAL SUBSISTENCE FISHERY IN THE RIPARIAN LIVELIHOODS - M, SAJINA A; SUDHEESAN, D; SAMANTA, S; Paul, S K; BHOWMICK, S; Nag, S K (Journal of the Inland Fisheries Society of India, 2020)
Many species of prolific breeding fishes support massive biomass of juveniles during and just after their peak breeding season. This kind of huge standing stock at a particular season facilitate small scale artisanal or subsistence fisheries specifically targeting these stocks, which extent for very shortduration. In inland aquatic systems like reservoirs and streams with riparian fisher folk, the opportunity to exploit the juvenile population is high depending upon the approachability of the water bodies and livelihood options of the riparian fishers. In case the situation is similar to the well-known adage ‘the fishery is the activity of last resort’, the probability for such small scale juvenile fishery to exist is very high. Many a times, small scale seasonal fisheries go unnoticed and their relevance and contribution to the livelihoods of riparian population is undermined, especially in the remote inland water bodies such as reservoirs. Such sort of intense but very seasonal targeted fishing activity wasobserved in Hirakud reservoir situated in the state of Orissa in north eastern India.